2018
DOI: 10.1136/jclinpath-2018-205026
|View full text |Cite
|
Sign up to set email alerts
|

Improving serum calcium test ordering according to a decision algorithm

Abstract: AimTo detect differences in the pattern of serum calcium tests ordering before and after the implementation of a decision algorithm.MethodsWe studied patients admitted to an internal medicine ward of a university hospital on April 2013 and April 2016. Patients were classified as critical or non-critical on the day when each test was performed. Adequacy of ordering was defined according to adherence to a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…A review of ordering for in-hospital patients, published in 2017, found that: education had some impact on test ordering, but this was not sustained; feedback on comparative ordering practices among clinicians reduced frequent tests by around 11%, with another (small) study achieving 66% reduction in ionised calcium (but without much data on sustainability); and restriction on ordering within electronic systems reduced a set of common tests by 21% 29. More recently, a decision-recommendation algorithm for calcium testing for inpatients in a hospital Brazil decreased ordering by 23% 30…”
Section: Discussionmentioning
confidence: 99%
“…A review of ordering for in-hospital patients, published in 2017, found that: education had some impact on test ordering, but this was not sustained; feedback on comparative ordering practices among clinicians reduced frequent tests by around 11%, with another (small) study achieving 66% reduction in ionised calcium (but without much data on sustainability); and restriction on ordering within electronic systems reduced a set of common tests by 21% 29. More recently, a decision-recommendation algorithm for calcium testing for inpatients in a hospital Brazil decreased ordering by 23% 30…”
Section: Discussionmentioning
confidence: 99%